Use of Microbiota to Fight Mosquito-Borne Disease - Huang, Wei; Wang, Sibao; Jacobs-Lorena, Marcelo (Frontiers in Genetics, 2020)
Up to 700 million people are infected and more than a million die each year from mosquito-borne illness (Caraballo and King, 2014). With the limitation of progress toward elimination imposed by insecticide- and drug-resistance, combined with the lack of vaccines, innovative strategies to fight mosquito-borne disease are urgently needed. In recent years, the use of mosquito microbiota has shown great potential for cutting down transmission of mosquito-borne pathogens. Here we review what is known about the mosquito microbiota and how this knowledge is being used to implement new strategies for the control of mosquito-borne diseases. We also discuss the challenges for the eventual release of genetically-modified symbionts in the field.